A randomized intervention study to evaluate the effect of calcitriol therapy on the renin-angiotensin system in diabetes. (February 2018) - Zaheer, Sarah; Taquechel, Kiara; Brown, Jenifer M; Adler, Gail K; Williams, Jonathan S; Vaidya, Anand
Background: Prior studies suggest that vitamin D therapy may decrease cardiovascular disease risk in type 2 diabetes (T2DM) by lowering renin-angiotensin system (RAS) activity. However, randomized human intervention studies to evaluate the effect of vitamin D receptor (VDR) agonists on RAS activity are lacking. Objective: The objective of this article is to investigate the effect of direct VDR activation with calcitriol on circulating RAS activity and vascular hemodynamics in T2DM. Methods: A randomized, double-blinded, and placebo-controlled study wherein 18 participants with well-controlled T2DM without chronic kidney disease (CKD) were administered calcitriol or placebo for three weeks was conducted. Outcome measures included plasma renin activity (PRA), serum and urinary aldosterone, mean arterial pressure (MAP) before and after an infusion of angiotensin II, and renal plasma flow (RPF) via para -aminohippurate clearance. Results: Despite an increase in 1, 25(OH)2 D with calcitriol administration (45.4 to 61.8 pg/ml, p = 0.03) and no change with placebo, there were no significant differences in PRA, serum or urinary aldosterone, baseline and angiotensin II-stimulated MAP, or basal and angiotensin II-stimulated RPF between interventions. Conclusion: In this randomized and placebo-controlled study in participants with T2DM without CKD, calcitriol therapy to raise 1, 25(OH)2 D levels, when compared with placebo, did not significantly change circulating RAS activity or vascular hemodynamics.